Identifying the reaction mechanism of oil-shale self-heating retorting by thermal analysis techniques. (15th November 2015) - Guo, Hongfan; Pei, Yansong; Wang, Kuikui; Cheng, Qiuxiang; Ding, Yang; Jin, Ze; Yang, Yindong; Wu, Qicheng; Liu, Yunyi
Highlights: Noticeable amount of residual carbon (RC) byproduct is produced in anaerobic retorting. While RC can be utilized in self-heating retorting (SHR) via in-situ reacting with air to release heat used for retorting. In-situ utilizing RC partly explains "why SHR provides heat for itself but without obviously lost oil yield". A plausible reaction mechanism of SHR is also put forward. Abstract: Oil shale (OS), from which petroleum-like shale oil can be obtained via retorting, is one of the most promising alternative fossil fuels due to its huge reserve. A main obstacle to OS retorting is the required high-energy input, particularly for underground retorting. Recently a low-energy-input route via self-heating retorting (SHR) was developed (Guo et al., 2013 and 2014). However, its unclear reaction mechanism hinders its further development. Herein, the reaction mechanism of SHR was analyzed by using Huadian OS and thermal analysis techniques. The results suggest anaerobic retorting (AR) used for preparing shale oil produces substantial residual carbon (RC) byproduct, and the heat contained in RC is more than the energy input needed by an AR process. While in SHR process, by reaction-kinetics control, part of kerogen is first pyrolized into oil and RC before exposed to air, and then RC in-situ reacts with the diffused air to release heat for progressing SHR and replacing external heat supply. In-situ utilizing RC by SHR process partly explains why SHR itself provides heat to increase retorting temperature but without obviously lost shale-oil yield.